2010
DOI: 10.1111/j.1574-0862.2010.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating consumer willingness to pay for food quality with experimental auctions: the case of yellow versus fortified maize meal in Kenya

Abstract: Biofortification of maize with provitamin A carotenoids is a new approach to the alleviation of vitamin A deficiencies in Africa. Unfortunately these varieties are yellow or orange, while consumers generally prefer white. Consumer willingness to pay for yellow and fortified maize was compared in experimental auctions in three regions in Kenya. The premium that consumers are willing pay for fortified maize (24%) was higher than the discount they require to buy yellow maize (11%), and in one zone consumers prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(130 citation statements)
references
References 33 publications
7
123
0
Order By: Relevance
“…Indeed, food is by far the most commonly auctioned item, where valuation dimensions include quality attributes (e.g., marbling in pork chops), production conditions (e.g., organic, genetically modified organisms, growth hormones), and risk and information (e.g., food safety) (Alfnes and Rickertsen 2003;Hayes, et al 1995;Melton, et al 1996). In developing countries, experimental auctions have shed light on heterogeneity of valuation of health and nutrition products such as bed nets, fortified foods, and infant foods of certified quality (De Groote, et al 2010;Dupas 2010;Hoffmann, et al 2009;Masters and Sanogo 2002). Our experimental auction approach to understanding farmers' valuation of LLL builds on these recent efforts and incorporates a WTP-conditioned lottery to enable the rigorous evaluation of LLL impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, food is by far the most commonly auctioned item, where valuation dimensions include quality attributes (e.g., marbling in pork chops), production conditions (e.g., organic, genetically modified organisms, growth hormones), and risk and information (e.g., food safety) (Alfnes and Rickertsen 2003;Hayes, et al 1995;Melton, et al 1996). In developing countries, experimental auctions have shed light on heterogeneity of valuation of health and nutrition products such as bed nets, fortified foods, and infant foods of certified quality (De Groote, et al 2010;Dupas 2010;Hoffmann, et al 2009;Masters and Sanogo 2002). Our experimental auction approach to understanding farmers' valuation of LLL builds on these recent efforts and incorporates a WTP-conditioned lottery to enable the rigorous evaluation of LLL impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Both authors found a preference for white unfortified maize over the yellow-orange biofortified maize, which is reflected in the consumers' WTP (De Groote et al, 2011).…”
Section: Gm Food Attributes and Consumer Acceptancementioning
confidence: 99%
“…Information about the improved folate concentrations and the associated benefits might increase WTP for FBR, as is the case with conventional biofortified crops (De Groote et al, 2011), but may be negatively affected when consumers are aware of the GM technology that is implemented (Depositario et al, 2009a). In this WTP study, information about the folate content, the folate benefits and the GM nature of the product is provided through separate information rounds.…”
Section: Information Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 8 118 , for example, are partly due to the high prevalence rate of vitamin A deficiency in this region. Also De Groote et al 119 elicited valuations for a crop with a higher vitamin content, namely willingness-to-pay for biofortified corn. Their results showed that consumers in Kenya are prepared to pay 24 % more for corn if it would be enriched with provitamin A.…”
Section: Consumer Preferences For Gm Biofortified Ricementioning
confidence: 99%